Capital structure determinants of Islamic hybrid securities / Mohamad Nizam Jaafar - Jaafar, Mohamad Nizam (2015)
Firms raise their capital via the common external funds either debt or equity. However, under certain conditions, firms are required to issue more complex financial engineering instruments namely hybrid securities. Literatures showed that very little studies have been conducted on Islamic Capital Market and in establishing the determinants of hybrid securities. Based on theories of capital structure which related to non hybrid capital structure, the variables and the models on hybrid financing are developed. In further filling the gap of the preceding studies, we developed a dynamic model by incorporating important variables that are associated to macroeconomic indicators that are economic growth (GDP), interest rate (BFR), level of stock market development and bond market development. Several estimation models are developed namely convertible bond plus loan stock which signify for debt treat hybrid (model 1) and warrant which is represent equity treat hybrid (model 2) respectively. This study employs the static model via panel ordinary least square (OLS), fixed effects model and random effects model to identify the best estimation model. Besides that, the study also include dynamic model via General Method of Moment (GMM) - first and second generation GMM, to get the most excellent model. From the analysis of static model, it reveals that the best estimation models for both hybrid securities are from model 1 and 2 of fixed effect model. Meanwhile from dynamic analysis, system GMM is considered the most excellent model. As inferences to the body of knowledge, this research has established several factors that are significant in determining hybrid securities for both debt and equity feature hybrid respectively. For Model 1, risk and profitability is considered the most determinant considerations for issuing convertible bond and loan stock in conjunction with its highest coefficient among all the variables under review. Meanwhile for Model 2, financial risk and adverse financial position is the most determinant factors for issuing hybrid equity. These results suggest that, the firms that expose with high risk but low profitable position will opt for warrant for expansion and the firms that have high risk and strong financial position will choose convertible bond or loan stock. Since the high risk firms but profitable are difficult to secure additional credit facility from the financial institutions, there always opt for hybrid security of convertible bond as proposed by risk shifting theory where hybrid securities allow the high risk firm to further venture into riskier business. For high risk but adverse financial position will opt for warrant securities. Meanwhile, the result from model 1 also support the sequential financial problem theory where the hybrid securities enable the profitable firms to venture intopositive NPV project by issuing convertible bond as it offer lower coupon rate as compare to the normal debt rate. These findings can be considered as indication that firms generally use hybrid securities implied by sequential financial problem theory and risk shifting in addition to other capital structure theories such as trade off, pecking order and back door listing.